A Legal Analysis of the Urgency to Ratify the Border Crossing and Border Trade Agreements between Indonesia and Malaysia - Dhafin Riyasy Ishak; Achmad Jaka Santos Adiwijaya; Nyi Mas Gianti Bingah Erbiana (JURNAL ILMIAH LIVING LAW, 2026)
This study analyzes the urgency of ratifying the Border Crossing Agreement (BCA) and Border Trade Agreement (BTA) between Indonesia and Malaysia and examines the inconsistencies between Indonesian legal practice and the theoretical framework governing the ratification of international treaties. Using a normative and descriptive legal method with statutory, comparative, and conceptual approaches, this research evaluates the application of Law Number 24 of 2000 on International Treaties in relation to the unratified status of BCA and BTA despite their essential role in regulating cross border mobility and local trade in the border regions of Kalimantan. Data were obtained through an extensive literature study supported by juridical analysis in accordance with the characteristics of normative legal research. The findings reveal that although Indonesia has incorporated several substantive elements of BCA and BTA through ministerial regulations, such partial adoption does not comply with the principles of treaty ratification defined under national law and the Vienna Convention on the Law of Treaties 1969. The absence of formal ratification results in legal uncertainty, administrative inconsistency, and insufficient protection for border communities. This study concludes that formal ratification of BCA and BTA is essential to ensure legal certainty, support equitable economic development, and enhance the effectiveness of cross border cooperation between Indonesia and Malaysia. Strengthening the ratification mechanism also becomes necessary to reinforce Indonesia’s credibility in fulfilling its international obligations and to align cross sectoral governance in strategic border regions.